NANOEMULSION AS A DRUG DELIVERY SYSTEM OF ANTICANCER DRUG - SOUMIK MAITY; INDRANIL BANERJEE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Nanoemulsions are isotropic systems made up of nanoscale droplets (about 200 nm in size) created by combining two immiscible liquids with the aid of emulsifiers. They are often regarded as harmless excipients and are made to enhance the release of active medicinal compounds. Improving drug distribution to specific areas is the main goal of employing nanoemulsions in cancer treatment. In addition to increasing bioavailability, nanoemulsions reduce adverse effects on healthy cells by encasing medications in a closed structure. This is especially crucial because, in the absence of such formulations, different medications fall short of their intended targets. The study shows that by increasing the solubility and bioavailability of anticancer medications, nanoemulsions can greatly improve their delivery. This is important because a lot of anticancer medications have low solubility, which reduces their ability to effectively target cancer cells. Nanoemulsions have been shown to effectively target tumor cells while minimizing the impact on healthy tissues. This targeted approach helps overcome the common issue of multidrug resistance seen in cancer treatments, as the nanoemulsions can be modified with specific ligands to focus on tumor cells. Targeting tumor cells and preventing multidrug resistance are two benefits of using nanoemulsions. Besides, hydrophilic and hydrophobic compounds can be encapsulated in nanoemulsions to satisfy a range of needs. Therefore, nanoemulsions are a promising new approach to cancer treatment. This review provides an overview of nanoemulsion in cancer therapeutics, aiming to highlight the current status of this technology.